Social media exposure and paragraph writing of pre-service students - Tomas, Rowena R. Sto.; Dulin, Alvin T. (Linguistics and Culture Review, 2021)
This research determines the relationship between the paragraph writing performance and the social media exposure of the pre-service teachers of the College of Teacher Education at Cagayan State University located in the Northern Philippines. The respondents are fourth year college students who specialize in TLE, English, Social Science and Mathematics. Through a descriptive quantitative research design, this research finds out that the pre-service teachers need improvement in mechanics, grammar, vocabulary and language use. Respondents who are generally exposed to social media once or twice a week, who use mostly their mobile phones at home in accessing the Facebook and messenger for searching different sources for information and learning prove to help improve their written outputs especially in their grammar and writing mechanics.